1992
DOI: 10.1097/00006842-199207000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral clusters and coronary heart disease risk.

Abstract: The purpose of the present study was to empirically identify individuals who differed in their patterns of components derived from the structured interview (SI), and to evaluate whether individuals characterized by the different patterns varied in terms of their risk for coronary heart disease (CHD). The present study represents a reanalysis of data from the Western Collaborative Group Study in which components of Type A were individually related to risk for CHD. Subgroups of individuals who differed in the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 17 publications
2
48
0
Order By: Relevance
“…The results for aggressiveness and cholesterol are congruent with those obtained by Dujovne and Houston (1991) and further support the notion that hostility-related variables may confer risk for CHD, at least for men. The results for dominance and cholesterol, in conjunction with the findings of studies relating dominance to various cardiovascular end points (Deary et al, 1994;Houston et al, 1992;Manuck et al, 1989;Smith et al, 1990), suggest that psychosocial variables in addition to hostility may confer risk for CHD, again at least for men.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The results for aggressiveness and cholesterol are congruent with those obtained by Dujovne and Houston (1991) and further support the notion that hostility-related variables may confer risk for CHD, at least for men. The results for dominance and cholesterol, in conjunction with the findings of studies relating dominance to various cardiovascular end points (Deary et al, 1994;Houston et al, 1992;Manuck et al, 1989;Smith et al, 1990), suggest that psychosocial variables in addition to hostility may confer risk for CHD, again at least for men.…”
Section: Discussionmentioning
confidence: 86%
“…Effortful attempts to exert dominance or social control have been found to be associated with enhanced cardiovascular reactivity (Smith et al, 1989;Smith et al, 1990) which has been hypothesized to contribute to hastening of CHD (Williams and Barefoot, 1988). Further, in a reanalysis of data derived from the SI and the 8.5-year follow-up of the Western Collaborative Group Study by Houston et al (1992), it was found that, independent of hostility, individuals were at increased risk for CHD who exhibited a group of verbal behaviors (viz., quick responses, interrupting the interviewer) that have been associated with social control or dominance in other research (Burger, 1992;Dembroski et al, 1984;Ferguson, 1977;Holleran, 1994;Linkey and Firestone, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…8 Findings of the Multiple Risk Factor Intervention Trial especially undermined a confidence in an etiologic role of Type A behavior. 9 Studies published in the 1990's were few in number, and reported both positive 10,11 and negative findings. 12,13 In 1999, Hemingway and Marmot concluded in their clinical review that Type A behavior has a minor etiologic role in coronary heart disease among healthy adults, but no prognostic significance in patients with coronary heart disease.…”
mentioning
confidence: 99%
“…hostility [37], social isolation [38], and job stress [39]). Other promising risk factors supported by less comprehensive literature also have an explicitly interpersonal focus, such as social dominance (40)(41)(42). For some more recently identified risk factors, other research indicates that interpersonal factors might be important.…”
Section: Two Roles Of Cardiovascular Reactivitymentioning
confidence: 99%